A melancolia revolucionária de Walter Benjamin e a Weltanschauung romântica - Messerschmidt, Marcos Lentino (2019)
The present work seeks to investigate and establish the relationship between the Benjaminian melancholy and the romantic Weltanschauung (worldview), as formulated by Michael Löwy and Robert Sayre in Romanticism Against the Tide of Modernity. To do so, we will try to situate the thought of Walter Benjamin in relation to the so-called revolutionary and /or utopian romanticism. At the beginning of the work is presented a concise history of melancholy, in addition to the historical rescue of this realized by Walter Benjamin in The Origin of German Tragic Drama. Next, the foundations of the vision of Michael Löwy and Sayre on the romanticism are presented, besides the outline of a typology of the romanticism formulated by the authors to finally arrive at the definition of what would be the omantic Weltanschauung according to them. In the final part of the present work, we try to demonstrate how the melancholy of Walter Benjamin transpires in his texts, relating it to the romantic worldview, in order to investigate how much the Benjaminian melancholy can be considered revolutionary.